Genetically Modified Tomatoes - K Das, Prafulla (International Journal of Psychosocial Rehabilitation, 2025)
Tomato, also called as Lycopersiconesculentum Mill belongs to family Solanaceae. Tomato is a diploid plant with 24 chromosomes. Tomato varieties have been improved to a great extent by practicing mating, hybridization, self-pollination and by understanding shortage of gene duplication, by easily identifying the chromosome no.12. New methodology has been adopted like genome mapping of “agronomic characters” and implementation of backcross with advanced technique to enhance tomato crop along with understanding domestication process. Breeding in tomato plant is done to improve production & quality of fruit and make the same, pests & disease resistant. Conventional breeding methods adopted, didn’t found to enhance tomato productivity; therefore, “molecular genetics and molecular markers techniques” are adopted and work is carried out on these. Thus, combination of conventional breeding & “plant biotechnology” methodology along with the genetic markers, “marker assisted selection” may be recognised as an important ornament for breeding tomato.